Pelatihan dan Pendampingan Penyusunan Proposal Program Kreativitas Mahasiswa (PKM) di Lingkungan Universitas Pendidikan Mandalika - Baiq Muli Harisanti; Titi Laily Hajiriah; Sumarjan Sumarjan; Akhmad Sukri; Faizul Bayani Aziz; Ismul Azim (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Students of the Mandalika University of Education (UNDIKMA) each year propose a Student Creativity Program (PKM) proposal from various existing schemes. Students of the Faculty of Science, Technique, and Applied Science Mandalika University of Education each year win PKM grants. In 2021, students from the Department of Biology Education won a PKM-RE scheme, continuing in 2022, the same students won 1 incentive scheme, namely PKM-AI. However, so far the participation of Mandalika University of Education students in compiling PKM proposals is still relatively low, because there are no more than 5 teams proposing PKM each year. Therefore, the Department of Biology Education Lecturer team took the initiative to conduct training and assistance in preparing PKM proposals for 2023, with the hope that after this training and assistance, the PKM team proposing grants this year will experience an increase. The purpose of this service program is the preparation of PKM proposals from various PKM schemes offered by the Directorate General of Higher Education and Technology up to the submit stage. The results of these training and mentoring activities show an increase in student interest in proposing PKM. This is evidenced by the increasing number of submitted PKM proposals. Apart from that, the enthusiasm of the students to learn and read various kinds of articles was also seen as a reference for their respective proposals.